2020
DOI: 10.1126/science.abe3255
|View full text |Cite
|
Sign up to set email alerts
|

An ultrapotent synthetic nanobody neutralizes SARS-CoV-2 by stabilizing inactive Spike

Abstract: The SARS-CoV-2 virus enters host cells via an interaction between its Spike protein and the host cell receptor angiotensin converting enzyme 2 (ACE2). By screening a yeast surface-displayed library of synthetic nanobody sequences, we developed nanobodies that disrupt the interaction between Spike and ACE2. Cryogenic electron microscopy (cryo-EM) revealed that one nanobody, Nb6, binds Spike in a fully inactive conformation with its receptor binding domains (RBDs) locked into their inaccessible down-state, incap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
443
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(484 citation statements)
references
References 63 publications
24
443
0
Order By: Relevance
“…The affinity of NIH-CoVnb-112 in monomeric form is substantially better than the monomeric form of previously reported candidate nanobody therapeutics for SARS-CoV-2: 39 nM for monomeric VHH72 24 , ~ 50 nM for monomeric Ty1 23 , 30.7 nM for monomeric Sb#14 21 , 10 nM for monomeric Sb23 22 , and incompletely reported but likely lower than 1B and 3F 27 . The affinity and blocking potency of NIH-CoVnb-112 will likely be even higher when formulated into dimeric, trimeric, or other protein engineered constructs 27,30,32,33 . Importantly, these nanobody therapeutics may be delivered via inhalation 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The affinity of NIH-CoVnb-112 in monomeric form is substantially better than the monomeric form of previously reported candidate nanobody therapeutics for SARS-CoV-2: 39 nM for monomeric VHH72 24 , ~ 50 nM for monomeric Ty1 23 , 30.7 nM for monomeric Sb#14 21 , 10 nM for monomeric Sb23 22 , and incompletely reported but likely lower than 1B and 3F 27 . The affinity and blocking potency of NIH-CoVnb-112 will likely be even higher when formulated into dimeric, trimeric, or other protein engineered constructs 27,30,32,33 . Importantly, these nanobody therapeutics may be delivered via inhalation 34 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, several Nbs against SARS-CoV-2 were reported for their in vitro activities, but none of them have been evaluated via intranasal administration in animal models [21][22][23][24][25][26] . In the current report, anti-sera specific for RBD were elicited by immunizing an alpaca with SARS-CoV-2 spike glycoprotein (S).…”
Section: Sars-cov-2 Is Transmitted Via the Upper Respiratory Tract 17mentioning
confidence: 99%
“…The second category of neutralizing mAbs were identified from previously isolated anti-SARS-CoV mAbs by testing their cross-reactivities to SARS-CoV-2 antigens (Ejemel et al, 2020;Huo et al, 2020;Pinto et al, 2020;Tai et al, 2020;Tian et al, 2020;Wec et al, 2020;Yuan et al, 2020b). The third category of neutralizing mAbs were developed in humanized mice by immunizing with S protein (Ejemel et al, 2020;Hansen et al, 2020;Wang et al, 2020a), and the fourth category of mAbs were identified by panning of phage or yeast-displayed libraries (Liu et al, 2020b;Lv et al, 2020;Noy-Porat et al, 2020;Schoof et al, 2020;Sun et al, 2020;Wu et al, 2020b;Yuan et al, 2020a;Zeng et al, 2020).…”
Section: Neutralizing Monoclonal Antibodies To Sars-cov-2mentioning
confidence: 99%